2021
DOI: 10.1371/journal.pone.0250695
|View full text |Cite
|
Sign up to set email alerts
|

Description and comparison of the skin and ear canal microbiota of non-allergic and allergic German shepherd dogs using next generation sequencing

Abstract: Atopic dermatitis is one of the most common skin diseases in dogs. Pathogenesis is complex and incompletely understood. Skin colonizing bacteria likely play an important role in the severity of this disease. Studying the canine skin microbiota using traditional microbiological methods has many limitations which can be overcome by molecular procedures. The aim of this study was to describe the bacterial microbiota of the skin and ear canals of healthy non-allergic and allergic German shepherd dogs (GSDs) withou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
29
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(30 citation statements)
references
References 74 publications
1
29
0
Order By: Relevance
“…Previous reports have shown that members of Brevibacterium are common in the skin and hair of multiple animals. For instance in areas such as the axilla and the groin of dogs (German shepherds) Brevibacterium showed to be one of the most dominant bacteria inhabiting these habitats (Apostolopoulos et al ., 2021). Interestingly, the high abundance of these genera has been associated with wildlife mammals such as mice (Belheouane et al ., 2020).…”
Section: Resultsmentioning
confidence: 99%
“…Previous reports have shown that members of Brevibacterium are common in the skin and hair of multiple animals. For instance in areas such as the axilla and the groin of dogs (German shepherds) Brevibacterium showed to be one of the most dominant bacteria inhabiting these habitats (Apostolopoulos et al ., 2021). Interestingly, the high abundance of these genera has been associated with wildlife mammals such as mice (Belheouane et al ., 2020).…”
Section: Resultsmentioning
confidence: 99%
“…Few publications to date have investigated the microbiota of dogs with skin allergies [24][25][26][27] . Using 16S rRNA gene amplicon sequencing, it has been reported that the nares of allergic dogs had lower species richness compared to healthy dogs 24 .…”
mentioning
confidence: 99%
“…Furthermore, studies have reported a decrease in bacterial diversity and an increase in the relative abundance of the Staphylococcus genus on the skin of dogs with dermatitis compared to healthy dogs 24,25,27 . Despite this, Staphylococcus is also considered to be the predominant genus on healthy dog's skin but with varying relative abundance, in addition to Corynebacterium, Kocuria, Macrococcus, Porphyromonas, Propionibacterium, Pseudomonas, and Streptococcus [24][25][26][27] . Interestingly, a previous study has investigated the effects of MRSA and MSSA colonisation on the lesional skin microbiota of humans with AD, and determined that those colonised with MRSA had reduced microbial diversity compared to MSSA colonisers 30 .…”
mentioning
confidence: 99%
“…For instance, canine patients with otitis have microbial dysbiosis with increases in the yeast M. pachydermatis and increased Staphylococcus and Streptococcus. 4 Devon Rex and Sphynx cats, which often suffer from seborrheic dermatitis, have higher carriage rates of Malassezia spp, even in the absence of skin lesions. 75 Several fungal and oomycete species can penetrate through skin defects and are responsible for causing superficial and/or deep infections, occasionally resulting in systemic disease.…”
mentioning
confidence: 99%
“…For instance, canine patients with otitis have microbial dysbiosis with increases in the yeast M. pachydermatis and increased Staphylococcus and Streptococcus . 4 Devon Rex and Sphynx cats, which often suffer from seborrheic dermatitis, have higher carriage rates of Malassezia spp , even in the absence of skin lesions. 75…”
mentioning
confidence: 99%